Student Nurses Knowledge of Needle Stick Injuries at a Private Institute, Karachi: Nurses Knowledge of Needle Stick Injuries - Ali, Mahboob; Bibi, Afsha; Khan, Jehangir; Arshad, Shaheen; Durdana, Mehnaz; Musafir, Yasmeen (Pakistan Journal of Health Sciences, 2023)
Needle Stick Injuries (NSI) are wounds penetrated to the skin by needles which can lead to infectious diseases such as Hepatitis B, C, and Human Immunodeficiency virus. Objectives: To determine the student nurses’ knowledge of NSI at a private nursing institute in Karachi. Methods: Descriptive cross-sectional study design was used. A total of 67 participants were recruited through the purposive sampling technique. Data were collected through a valid and reliable questionnaire from September to November 2022. Results: Study results showed that 41.8% of participants were males and 58.2% were females. The majority of the participants, 62.7%, were between 20-30 years of age and had an experience of 5-10 years. 62.7% of participants have taken the vaccine against the Hepatitis B virus. Around half (53.7%) of the participants were exposed to needle stick injuries (NSI) during clinical rotations. Knowledge results showed that 22.4% of nursing students had a good level of knowledge, 17.9% moderate, and 59.7% had a low level of knowledge regarding NSI. The association was found only between clinical experience and student nurses’ knowledge. Conclusions: Based on the findings, high prevalence of NSI, a low level of knowledge of NSI among students, and a low immunization rate of the Hepatitis B vaccine. Therefore, the institute and hospitals should conduct educational training programs and workshops to increase the knowledge level of nursing students regarding NSI and an immunization drive against Hepatitis B to protect them from the deadly virus